The Impact of Inquiry-Based Learning on Motivation and Foreign Language Anxiety in EFL Learners - Juan Manuel Castro-Carracedo (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Inquiry-Based Learning (IBL) has increasingly been recognized as an effective pedagogical approach for enhancing learner engagement and addressing affective barriers in second language acquisition. This study explores the impact of IBL on motivation and foreign language anxiety among intermediate EFL learners in a Spanish higher education context. Using a quasi-experimental pre-test/post-test design, 48 participants were randomly assigned to experimental and control groups. The experimental group completed an eight-week IBL program structured around exploratory tasks that encouraged questioning, collaboration, and autonomous problem solving, while the control group followed conventional instruction. Data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS) and the Attitude/Motivation Test Battery (AMTB), administered before and after the intervention. Results revealed significant increases in motivation and substantial reductions in anxiety among learners exposed to IBL, with large effect sizes supporting the robustness of the findings. The approach fostered a supportive learning environment in which students displayed higher levels of confidence, intrinsic motivation, and willingness to communicate. These results suggest that IBL not only enhances linguistic development but also functions as an affective regulator, promoting emotional resilience and engagement. The study highlights the potential of inquiry-based methodologies to cultivate more dynamic, autonomous, and emotionally positive learning experiences in EFL classrooms.